A Population of Projection Neurons that Inhibits the Lateral Horn but Excites the Antennal Lobe through Chemical Synapses in Drosophila - Shimizu, Kazumichi; Stopfer, Mark (Frontiers in Neural Circuits, 2017)
In the insect olfactory system, odor information is transferred from the antennal lobe (AL) to higher brain areas by projection neurons (PNs) in multiple AL tracts (ALTs). In several species, one of the ALTs, the mediolateral ALT (mlALT), contains some GABAergic PNs; in the Drosophila brain, the great majority of ventral PNs (vPNs) are GABAergic and project through this tract to the lateral horn (LH). Most excitatory PNs (ePNs), project through the medial ALT (mALT) to the mushroom body (MB) and the LH. Recent studies have shown that GABAergic vPNs play inhibitory roles at their axon terminals in the LH. However, little is known about the properties and functions of vPNs at their dendritic branches in the AL. Here, we used optogenetic and patch clamp techniques to investigate the functional roles of vPNs in the AL. Surprisingly, our results show that specific activation of vPNs reliably elicits strong excitatory postsynaptic potentials (EPSPs) in ePNs. Moreover, the connections between vPNs and ePNs are mediated by direct chemical synapses. Neither pulses of GABA, nor pharmagological, or genetic blockade of GABAergic transmission gave results consistent with the involvement of GABA in vPN-ePN excitatory transmission. These unexpected results suggest new roles for the vPN population in olfactory information processing.